A rheological approach to 3D printing of plasma protein based doughs - Alvarez-Castillo, E. (2021)
3D-printing, also known as additive manufacturing, is a polymeric processing technique whose use has been increasing strongly in recent decades. Because of its customizing potential, it is being widely applied in a great variety of fields, such as medicine, engineering, microelectronic, or food. The present work was focused on the determination of the rheological properties required for certain protein-based doughs (from blood plasma, pea and soy) to flow adequately during the 3D-printing process. Eventually, the formulations that resulted in conveniently shaped items, i.e., that reproduced the desired pattern, were selected. Using glycerol (Gly) as a plasticizer, the printability of doughs with different porcine plasma protein (PPP) contents was initially tested by rheology methods. Only doughs with a PPP content comprised between 42.5 and 47.5 wt % resulted in a successful printing. Then, part of PPP was replaced by a pea protein concentrate (PPC) or a soy protein isolate (SPI), keeping an overall biopolymer content of 45 wt % within the dough. Mixed doughs were properly printed, up to a PPC or SPI content of 10 or 15 wt % within the biopolymer fraction, respectively, displaying all printable doughs similar textural profiles (low firmness, high adhesivity). The building of printability maps for the protein-based doughs studied emphasizes the importance of controlling the rheological properties of protein-based doughs